THE FORMATION OF A CULTURE OF PROFESSIONAL OUTLOOK ON THE BASIS OF FORSEIT TECHNOLOGIES IN CLUSTER CONDITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is theoretically based on the importance of the system of professional ideals of the student's professional outlook, the intellectual and emotional approach to professional activity in the integration of the activities of foresight centers in a pedagogical cluster environment.